Review Metode Ekstraksi : Maserasi, Perkolasi, Infusa, Soxhlet, Refluks, Ultrasonic Assisted Extraction (UAE), dan Microwave Assisted Extraction (MAE) - Amaliya Bunga Dwiyanti; Devira Niken Putri Ferdinand; Mifta Dewi; Musa’adah Musa’adah; Noor Mila Wati; Rima Hindriani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Extraction is a crucial process for obtaining active compounds from natural materials, such as medicinal plants, spices, and other biomass. The success of the extraction process is greatly influenced by the method used, as each method has its own mechanism, efficiency, and yield. This study compared seven commonly used extraction methods: maceration, percolation, infusion, soxhletation, reflux, Ultrasound-Assisted Extraction (UAE), and Microwave-Assisted Extraction (MAE). Based on data collected from various scientific journals, it was found that modern methods such as UAE and MAE are capable of producing higher yields than conventional methods. Furthermore, both methods are more efficient in terms of extraction time and solvent usage, making them more environmentally friendly and suitable for industrial-scale applications. However, conventional methods such as maceration and percolation still play an important role, especially in initial research or in laboratories with limited equipment. For example, maceration is easy to perform, does not require high energy, and is suitable for heat-sensitive materials. Other factors that influence extraction results include the type of solvent, temperature, time, and the characteristics of the natural material itself. Therefore, the choice of extraction method must be tailored to the research objectives, the type of compound to be extracted, and the availability of resources and equipment. Combining several methods can also be considered to improve the efficiency and quality of the extraction results. It should be emphasized that extraction yield is influenced not only by the method, but also by the type of material, solvent, temperature, time, and particle size. Therefore, the choice of extraction method must be tailored to the nature of the material, the type of target compound, as well as the objectives and availability of resources. In some cases, a combination of extraction methods can also be used to increase efficiency and obtain optimal results.